Immune checkpoint inhibitors-related pancreatitis with fulminant type 1 diabetes mellitus: case report and literature review - Fang, Wei; Gao, Yang; Shi, Xiaoyan; Zhang, Xiaoran; Zhou, Shan; Zhu, Hongxia; Yan, Wei; Wang, Huanping (Frontiers in Immunology, 2023)
Immune checkpoint inhibitors (ICIs) are increasingly being used in the treatment of advanced human malignancies. ICIs-related adverse events, including pancreatitis and diabetes, have been individually characterized in the literature. The co-occurrence of ICIs-related pancreatitis with diabetes is rare and easily overlooked, but it is often severe or fatal. We present a patient with renal tumor resection who was treated with injection of the PD-L1 inhibitor toripalimab and eventually developed acute pancreatitis and fulminant type 1 diabetes mellitus. In addition, we conducted a literature review of ICIs-related pancreatitis with diabetes. The case in our report presented with paroxysmal abdominal pain and loss of appetite. Intravenous fluids and insulin infusion improved the patient’s pancreatitis and explosive hyperglycemia. This article suggests that ICIs can affect endocrine and exocrine functions of the pancreas, while providing information and new perspectives for the diagnosis and treatment of this challenging rare disease, helping inspire clinicians for the early identification and effective management of similar cases.